Crop diversification for weed management in organic arable cropping systems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Within the ERA-net CORE Organic Plus transnational programmes supported project PRODIVA producing of the information required for a better utilization of crop diversification for weed management in North European organic arable cropping systems was started. To fulfill the goal of this project- not to eradicate weed problems, which is unlikely to happen in any arable farming system, but to maintain a diversified and manageable weed flora that can support beneficial organisms- there were data from ongoing long-termed cropping system experiments from Latvia analyzed.It is hypothesised that: a) perennial weeds can be suppressed in the post-harvest period by improved cover crop establishment and pertinent selection of cover crop species; b) on-farm practices of crop diversification are related to weed pressure and species composition.On the bases on data from organic farm and ongoing long-termed cropping system experiment on weed dynamics in six-field crop rotations with cover crop was concluded that red clover as cover crop after the harvest period is effective to manage perennial weeds. In crop rotation with higher proportions of cereals weed infection growth in six-field rotation with 50% share of cereals up to 3.4, but with 33.3 %  share-up to 2.1 times.